2015 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2015
DOI: 10.1109/iros.2015.7353418
|View full text |Cite
|
Sign up to set email alerts
|

Identification of danger state for grasping delicate tofu with fingertips containing viscoelastic fluid

Abstract: Abstract-In this study, we experimentally investigated the process leading to fracture in tofu grasping by deformable fingertips filled with a fluid. In our previous papers [1, 2], we developed deformable fingertips using a rubber bag filled with a viscoelastic fluid, and presented a strategy for delicate tofu grasping without any advance knowledge about fracture. However, the predication point was close to fracture, and the prediction was then still a gamble. In order to realize fracture prediction at an earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…The diameter of the tubes was so small that the moving distance of water could be captured. Note that this method was valid when the pressure of the magnitude (the stiffness of the sensor part) was equal to or lower than the contact pressure (the stiffness of the target object/tissue), as indicated by previous experimental results [27]. Therefore, the system could have a dead zone where the water does not move even if load was applied to the system.…”
Section: A Target Situationmentioning
confidence: 72%
“…The diameter of the tubes was so small that the moving distance of water could be captured. Note that this method was valid when the pressure of the magnitude (the stiffness of the sensor part) was equal to or lower than the contact pressure (the stiffness of the target object/tissue), as indicated by previous experimental results [27]. Therefore, the system could have a dead zone where the water does not move even if load was applied to the system.…”
Section: A Target Situationmentioning
confidence: 72%
“…The surface of each fingertip was covered with nitrile rubber to ensure the same friction conditions. The fluid fingertip was the same as the one used for grasping fragile objects in our previous studies [13]. The stiffness of the fluid fingertip can be controlled by adjusting the fluid pressure inside the rubber bag.…”
Section: Mechanics Of Bent Sheetmentioning
confidence: 99%
“…In a human environment, a collision between humans and robots cannot be avoided, and thus, the surfaces of robots should be soft. With this in mind, we previously developed a robotic hand with a soft surface by filling a rubber bag with a viscoelastic fluid, and showed that the hand can grasp a wide variety of fragile objects [1]- [3]. Because of incompressibility, a uniform contact pressure distribution is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Y. Fujihira is could not be avoided. We then performed a detailed investigation of the pressure profile, and presented a new method was presented [3]. We showed that tofu could be grasped without fracturing at the point where the behavior of fluid pressure changed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation